2014
DOI: 10.1002/app.40606
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of 2‐methacryloyloxyethyl phosphorylcholine polymer nanofibers prepared via electrospinning for biomedical materials

Abstract: Electrospun nanofibers of poly (2‐methacryloyloxyethyl phosphorylcholine) (MPC) possessing excellent hemocompatibility were successfully fabricated first. These nanofibers were investigated as drug‐delivery vehicles for suppressing the acute thrombogenicity of vascular grafts to lower the risk of coronary artery disease by improving the graft patency rate; the graft patency rate is the percentage of patients who do not have any blockage in a graft after a stent‐graft treatment. We varied the MPC concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…It was found that the number of observed platelets increased, as the diameter increased regarding the nanofiber specimens. Our previous study revealed that the MPC fibers of large diameter had higher Ra (the arithmetic average of the roughness profile) than those of small diameter [7], indicating a close relationship between the surface roughness and the antithrombogenicity of MPC fibers.…”
Section: In Vitro Drug-release Tests From Mpc Nanofibers With Micropamentioning
confidence: 91%
See 3 more Smart Citations
“…It was found that the number of observed platelets increased, as the diameter increased regarding the nanofiber specimens. Our previous study revealed that the MPC fibers of large diameter had higher Ra (the arithmetic average of the roughness profile) than those of small diameter [7], indicating a close relationship between the surface roughness and the antithrombogenicity of MPC fibers.…”
Section: In Vitro Drug-release Tests From Mpc Nanofibers With Micropamentioning
confidence: 91%
“…MPC was mixed in ethanol to make 5 wt%, 7.5 wt%, and 10 wt% MPC solutions that were electrospun under the same experimental conditions studied before [7]. MPC nanofibers with the diameter of 164 nm, 637 nm, and 1270 nm were eventually synthesized for the platelet adhesion and activation tests.…”
Section: Materials Preparationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies (Chowdhury & Stylios, 2010;Deitzel et al, 2001;Maeda, Hagiwara, Yoshida, Hasebe, & Hotta, 2014;Theron, Zussman, & Yarin, 2004) have shown the effects of polymer concentration on the diameter and the morphology of the electrospun nanofibres. Higher polymer concentrations are more likely to produce uniform fibres with higher diameters.…”
Section: Effect Of Solution Concentration On Fibre Morphologymentioning
confidence: 99%